The Light Chain Defines the Duration of Action of Botulinum Toxin Serotype A Subtypes - Sabine Pellett; Marite Bradshaw; William H. Tepp; Christina L. Pier; Regina C. M. Whitemarsh; Chen Chen; Joseph Barbieri; Eric A. Johnson (2018)
ABSTRACT Botulinum neurotoxin (BoNT) is the causative agent of botulism and a widely used pharmaceutical to treat a variety of neurological diseases. BoNTs are 150-kDa protein toxins organized into heavy chain (HC) and light chain (LC) domains linked by a disulfide bond. The HC selectively binds to neurons and aids cell entry of the enzymatically active LC. There are seven immunological BoNT serotypes (A to G); each serotype includes genetic variants, termed subtypes. Only two subtypes, BoNT/A1 and BoNT/B1, are currently used as therapeutics. BoNT serotype A (BoNT/A) subtypes A2 to A8 show distinct potency, duration of action, and pathology relative to BoNT/A1. Specifically, BoNT/A3 possesses shorter duration of action and elicits distinct symptoms in mice at high toxin doses. In this report, we analyzed the roles of LC and HC of BoNT/A3 for duration of action, neuronal cell entry, and mouse pathology by using clostridium-derived recombinant hybrid BoNTs consisting of reciprocal LC and HC (BoNTA1/A3 and BoNTA3/A1). Hybrid toxins were processed in their expression host to a dichain BoNT consisting of LC and HC linked via a disulfide bond. The LC and HC defined BoNT potency in mice and BoNT toxicity for cultured neuronal cells, while the LC defined the duration of BoNT action in cell and mouse models. Protein alignment identified a previously unrecognized region within the LC subtype A3 (LC/A3) relative to the other LC serotype A (LC/A) subtypes (low primary acid homology [LPH]) that correlated to intracellular LC localization. This study shows the utility of recombinant hybrid BoNTs with new therapeutic potential, while remaining sensitive to antitoxins and therapies to native BoNT. IMPORTANCE Botulinum neurotoxins are the most potent protein toxins for humans and potential bioterrorism threats, but they are also widely used as pharmaceuticals. Within the large family of BoNTs, only two subtypes are currently used as pharmaceuticals, with a large number of BoNT subtypes remaining as untapped potential sources for unique pharmaceuticals. Here, two recombinant hybrid toxins were engineered, consisting of domains from two BoNT subtypes that possess distinct duration of action and activity in human neurons and mice. We define the functional domains responsible for BoNT action and demonstrate creation of functional hybrid BoNTs with new therapeutic potential, while remaining sensitive to antitoxins and therapies to native BoNT.